(1)X³+3X²+4X+2=0
x³+1+3x²+4x+1=0
(x+1)*(x²-x+1)+(x+1)*(3x+1)=0
(x+1)*(x²-x+1+3x+1)=0
(x+1)*(x²+2x+2)=0
因为x²+2x+2=x²+2x+1+1=(x+1)²+1>0
所以x=-1
(2)(X+1)^4+(X+3)^4-82=0
(X+1)^4-1+(X+3)^4-81=0
【(x+1)²+1】*【(x+1)²-1】+【(x+3)²+3】*【(x+3)²-3】=0
【(x+1)²+1】*(x+1+1)*(x+1-1)+【(x+3)²+3】*(x+3+3)*(x+3-3)=0
x*{【(x+1)²+1】*(x+2)+【(x+3)²+3】*(x+6)}=0
x*(x³+8x²+30x+56)=0 整理上面括号内
x*(x+4)*(x²+4x+14)=0
因为x²+4x+14=x²+4x+4+10=(x+2)²+10>0
所以x=0或-4
(3)2X^4-5X^3+4X^2-5X+2=0
2X^4-5X^3+2X^2+2X^2-5X+2=0
x²*(2x²-5x+2)+2x²-5x+2=0
(x²+1)*(2x²-5x+2)=0
(x²+1)*(x-2)*(2x-1)=0
因为x²+1>0
所以x=2或1/2